The Role of the Family Environment in the Upbringing of Children with Disabilities - Н.Ш. Умарова; Ф. Ш. Исакулов (European Science Publishing, 2023)
Helping children with limited opportunities to take their place in life, and the role of the family in this is highlighted.
Keywords: Family, child, help, limited opportunity, relationship.